2003
DOI: 10.1079/ajaa200235
|View full text |Cite
|
Sign up to set email alerts
|

An economic comparison of organic and conventional grain crops in a long-term agroecological research (LTAR) site in lowa

Abstract: Based on the interest of organic and conventional farmers in Iowa in long-term analysis of organic systems, the Neely-Kinyon Long-Term Agroecological Research (LTAR) site was established in 1998 to examine the agronomic and economic performance of conventional and organic systems, using certified organic production practices. We report the results of the economic analysis from 3 years of production (1999–2001). Using organic price premiums for organic crops, returns for corn within the organic corn-soybean-oat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 17 publications
6
95
1
2
Order By: Relevance
“…Economic returns mirrored those previously reported at other sites, with the organic rotations garnering, on average, twice the returns of the conventional rotation (Delate et al, 2013), and lower costs than conventional crops during transition (Delate, Duffy, Chase, Holste, Friedrich, & Wantate, 2003;Delate, Chase, Duffy, & Turnbull, 2006). Results from the LTAR experiment have been similar to other long-term trials, although LTAR organic yields have often exceeded those reported in the literature.…”
Section: The Long-term Agroecological Research (Ltar) Experiment Iowasupporting
confidence: 63%
“…Economic returns mirrored those previously reported at other sites, with the organic rotations garnering, on average, twice the returns of the conventional rotation (Delate et al, 2013), and lower costs than conventional crops during transition (Delate, Duffy, Chase, Holste, Friedrich, & Wantate, 2003;Delate, Chase, Duffy, & Turnbull, 2006). Results from the LTAR experiment have been similar to other long-term trials, although LTAR organic yields have often exceeded those reported in the literature.…”
Section: The Long-term Agroecological Research (Ltar) Experiment Iowasupporting
confidence: 63%
“…Meco et al (1998), Lacasta & Meco (2006), (Agreda & Abós, 2001) emphasize that organic cropping systems are more profitable than conventional systems even without considering the higher market prices for organic products. Delate et al (2003) obtained an increase of 25% in economic results for an organic system in relation to conventional agriculture with more profitable crops (cornoat-alfalfa) and more favourable climate conditions. Assuming a higher market price, the margins of the minimum input system (minimum (org), Figure 3) improve substantially (496%), almost five times higher than the conventional option.…”
Section: Economic Resultsmentioning
confidence: 96%
“…Moreover, we obtained similar results in a previous study including 25 analyses in eight locations in Spain with similar climatologically conditions over a four year period under normal soil fertility levels (Pardo, 2003). Of course, under these semiarid conditions, water is always the limiting factor and yields critically depend on the amount of rainfall in spring as stated by Moret et al (2007) and Díaz-Ambrona & Mínguez (2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In long-term experiments in Saskatchewan, Minnesota, and Iowa, organic systems had net returns greater than or equal to conventional systems, but these levels of return were dependent on organic premiums for at least some crops (Delate et al 2003;Delbridge et al 2011;Zentner et al 2011a). Income variability may be lower in organic systems (Pimentel et al 2005;Zentner et al 2011a).…”
Section: Organic Systemsmentioning
confidence: 99%